2018
DOI: 10.1111/sms.13090
|View full text |Cite
|
Sign up to set email alerts
|

Video analysis of acute injuries and referee decisions during the 24th Men's Handball World Championship 2015 in Qatar

Abstract: Although handball is a contact sport with a high risk of acute match injuries, their mechanisms have not yet been investigated. We aimed to describe the mechanisms of acute match injuries in elite male handball and evaluate referee performance in injury situations. Based on injury surveillance from the 24th Men's Handball World Championship 2015 in Qatar, injury situations and the referee decisions were identified on video footage. A total of 55 injury situations and 37 referee decisions were included for anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
2
11
0
3
Order By: Relevance
“…Previous studies, in other sports32 33 as well as in handball29 have suggested that stricter rule enforcement should be seriously considered in order to reduce the rate of injuries; however, we do not know how realistic it is for players to modify their playing style. Indeed, reducing aggressive play could result in an impaired performance.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies, in other sports32 33 as well as in handball29 have suggested that stricter rule enforcement should be seriously considered in order to reduce the rate of injuries; however, we do not know how realistic it is for players to modify their playing style. Indeed, reducing aggressive play could result in an impaired performance.…”
Section: Discussionmentioning
confidence: 93%
“…This finding is consistent with previous studies showing that more injuries occur while attacking than defending in the central positions of the field,1 28 29 meaning that players who participate more actively in goal-scoring attempts are at greater risk 1 18. In addition, based on systematic video analysis of injuries occurring during the 2015 Handball World Championship, Andersson et al 29 observed that the match referees were too lenient in their rule interpretation and suggested that stricter application of the rules (and potentially modifying some rules) could reduce the risk of acute match injuries, especially when an attacker performing a jump shot is tackled.…”
Section: Discussionmentioning
confidence: 99%
“…An implementable prevention strategy could be to allow matches continue into newasa more easily, to avoid excessive time spent in tachi waza. In some sports, for example handball, 26 video analysis has been used to better understand injury mechanisms. Injury situations identified on video footage together with injury surveillance and referee decisions would allow us to better understand injury mechanisms in Paralympic judo, and is therefore recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The game continues with fast breaks against the rearrangement of protection, which is an important strategic element in the modern handball. Specialists in foreign handball target their players to improve the tactical principles and strategy of the offensive game against unorganized protection, to adhere to special technical requirements for fast play, such as different variants of knowing and handing over the ball with one hand in all game situations [6,[47][48][49]. The throws of the ball into the goal are the culmination of the attacking action of the handball players, so their training is crucial.…”
Section: Discussionmentioning
confidence: 99%